(untitled) (Research, Society and Development, 2021)
The aim of the present study was to clinically assess the dental condition of patients admitted to an Intensive Care Unit (ICU). This is an exploratory, descriptive and cross-sectional study with dental evaluation of 40 patients admitted to the General ICU of the Fundação de Beneficência Hospital Cirurgia based in Aracaju-SE. Data were collected from medical records regarding age, sex, deleterious habits and the causal factor of hospitalization. The analysis of the oral condition was classified in three categories: good, regular and bad. It was found that 67.50% of the patients were female. Regarding the medical condition of the individuals, it was observed that the most common factor was respiratory, reaching 32.50% of them, followed by sepsis and neurological factor, which correspond to 17.50% and 15.00% of patients, respectively. As for the distribution of dental conditions, it was observed that 65.00% had a regular condition, 27.50% of the patients had a good classification and 7.50% had a poor condition. Regarding the lingual coating index according to the area, it was seen that only 5.00% and 17.50% of the patients did not have coating, while 22.50% had up to 1/3 of the tongue, 32.50% up to 2 / 3 of the language and 22.50% more than 2/3 of the language. In relation to the index of lingual coating according to thickness, 20% of individuals had thin coating, while 47.50% and 32.50% presented with visible and non-visible lingual papillae, respectively. The results reveal that the majority of patients admitted to the ICU had a regular dental condition, and the most prevalent oral foci were toothless abscesses and oral candidiasis.